2002
DOI: 10.1128/cdli.9.5.1039-1043.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Whole-Blood Analysis of Cellular Immunity in Patients with Active Coccidioidomycosis by Using the Antigen Preparation T27K

Abstract: Measurement of cellular immunity in human coccidioidomycosis has important diagnostic and prognostic implications. The coccidioidin skin test has been the standard for the measurement of this, but it is not available in the United States. We examined the utility of measuring surface expression of CD69 on T lymphocytes in whole blood incubated with the coccidioidal antigen preparation T27K as an alternative to the skin test. Seventy donors with active coccidioidomycosis were studied. The mean fluorescent intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…CD4 ϩ T cells (2.5 ϫ 10 6 ) and APCs (2.5 ϫ 10 6 ) were cocultured either in the presence of Coccidioides T27K antigen (40 g/ml medium) (46) or in medium alone and transferred to wells of a 24-well plate containing 1 ml of RPMI 1640 medium plus 10% (vol/vol) heat-inactivated FBS, 100 IU/ml penicillin, and 100 g/ml streptomycin. The T27K antigen is a multicomponent, soluble derivative of C. posadasii parasitic cell homogenates and has been shown to have protective activity against pulmonary coccidioidomycosis in mice (1). Supernatants of the stimulated immune T cells were collected after 48 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…CD4 ϩ T cells (2.5 ϫ 10 6 ) and APCs (2.5 ϫ 10 6 ) were cocultured either in the presence of Coccidioides T27K antigen (40 g/ml medium) (46) or in medium alone and transferred to wells of a 24-well plate containing 1 ml of RPMI 1640 medium plus 10% (vol/vol) heat-inactivated FBS, 100 IU/ml penicillin, and 100 g/ml streptomycin. The T27K antigen is a multicomponent, soluble derivative of C. posadasii parasitic cell homogenates and has been shown to have protective activity against pulmonary coccidioidomycosis in mice (1). Supernatants of the stimulated immune T cells were collected after 48 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 H]thymidine incorporation was measured using a scintillation counter (TopCount; Perkin-Elmer). T27K has been previously demonstrated to specifically distinguish Coccidioides-immune donors from nonimmune donors (11,12,33). PBMC from all individuals tested were activated by phytohemagglutinin.…”
Section: Cytokines and Antibodiesmentioning
confidence: 99%
“…More recently, in vitro studies have shown that peripheral blood T lymphocytes from individuals with well-controlled infection produce gamma interferon (IFN-␥) in response to coccidioidal antigen, while cells from individuals with disseminated disease do not (1). Failure of T lymphocytes to react to coccidioidal antigen in vitro is associated with a poorer clinical score among those with disseminated disease (2).…”
mentioning
confidence: 99%